الأفارقة الأمريكان وظروف الحرب الباردة - الموسوي، ربيع حيدر طاهر; الحسناوي، تغريد جاسم عطية (جامعة الكوفة - كلية التربية للبنات, 2023)
شهدت الولايات المتحدة الأمريكية تغيرات داخلية كانعكاس طبيعي لظروف الحرب الباردة، رافق ذلك نمو طبقة وسطى سوداء وظهور الدعوات المطالبة بحقوق الافارقة الأمريكان، من خلال الأحزاب والمنظمات التي كان البعض منها يحمل الأفكار الشيوعية، مما أثار حفيظة الحكومة الأمريكية التي قابلت ذلك بمواجهة عنيفة وتصفية لكل من تشك بأنه يحمل الأفكار الشيوعية، مما أدى إلى محاولات أخرى للزعامات السوداء تثبت فيها للحكومة الأمريكية سلامة موقفها ومعاداتها لكل من يحمل الأفكار الشيوعية. سعيا وراء حصولها على الحقوق كمواطنين من الدرجة الأولى. The United States has seen internal changes as a reflection of natural conditions of the Cold War, accompanied by the growth of a middle class black and the appearance of the calls for the rights of African Americans, through parties and organizations, some of which were carrying communist ideas, sparking the ire of the US government, which met this violent confrontation and the liquidation of each of the suspect that carries the ideas of communism, which led to other attempts of black leaders to prove the safety of the US government's stance and hostility anyone who carries communist ideas. In pursuit of gaining rights as citizens of the first class.
Keywords: الحرب الباردة -- الفكر الشيوعي -- التمييز العنصري -- الأفارقة الأمريكيون -- حقوق الإنسان